The ceques: Channel code in Cusco Incaico - Sherbondy, Jeanette E. (1986)
This "new" interpretation of the ceque system is actually about ten years old. I came in August 1975 to do anthropological research on current irrigation in the department of Cusco. On that occasion I observed that various types of artificial irrigation systems were maintained at the same time, from projects carried out recently by the State to very old systems. What most caught my attention was a canal whose waters irrigated the lands of the Socsu-Aucaille ayllu in the town of San Sebastián, very close to the city of Cusco.